Correlation between Self-Efficacy and Interpersonal Communication with Performance of Badminton Referees (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
A referee has a role to determine the quality and the comfort of a match. Therefore, a referee is expected to have a good self-efficacy and interpersonal communication. This study was aimed to examine the correlation between self-efficacy and interpersonal communication with the performance of badminton referees. This study involved 30 referees and used a questionnaire for measuring self-efficacy and interpersonal communication. The referee appraisal form provided by the Executive Board of the Indonesian Badminton Association (PB PBSI) was used to measure the performance of badminton referees. The results showed that there was a significant relationship between self-efficacy (X1) and interpersonal communication (X2) with the performance of badminton referees (Y) as indicated by the value of Fcount = 61.49 which is greater than Ftable = 3.34 and a coefficient value correlation of Ry1-2 = 0,91. The coefficient of determination was (Ry1-2)2 = 0,83, meaning that self-efficacy and intrapersonal communication had a contribution of 83% to the referee performance, whereas the 17% was influenced by other factors. This study showed that there was a correlation between self-efficacy and interpersonal communication with the performance of badminton referees. For this reason, to improve the performance of badminton referees, the elements of self-efficacy and communication should be included as materials in referee trainings.